„... och noterna hade du i hjärtat“: Stort och smått om musik i klingande form och på noter - Ternhag, Gunnar (Danish Yearbook of Musicology, 1996)
„... and you had the notes in your heart“. About music as it sounds and transcriptions of it Is it at all possible to write music down as it sounds? This question is the basis of the present article which attempts to give an answer on two levels: a theoretical and a practical. The theoretical discussion considers the relationship between music as it sounds and transcriptions of it. The article also deals with the practice of transcription – in particular, the consequences of the fact that the fiddler and the ballad singer were seldom visited more than once by a collector. In this connection, it must be emphasized that the collectors were not concerned with the non-musical expression. The central part of the article deals with the Swedish fiddler, Hjort Anders Olsson (1865-1952), and four transcriptions of the same instrumental piece („låt“) made by three collectors on different occasions. The transcriptions lay the foundation for a closer study, partly of the fiddler’s technique of variation, and partly of the transcriber’s way of understanding the music of the fiddler. It is clear from the fact that the music becomes more and more complex that Hjort Anders continuously modified his piece of music. The material shows, that the transcribers perceived the music differently when Hjort Anders played the same piece, for they wrote down the music differently when they apparently heard the same musical sequence. The conclusion is not unexpected, but the analysis of these four transcriptions exposes the problem of notating music as it sounds.